Effect of Nephelium lappaceum Fruit Flesh on Acute Toxicity and Behavioural Responses of Catla catla (Hamilton, 1822) Fingerlings - Madhina, V.; Ravichandran , R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Nephelium lappaceum, popularly known as ‘Rambutan’, is an evergreen tree. This plant has been used as traditional medicine, and the fruits have always remained a potential source of nutrients. The acute toxicity data has been used to derive water and feed quality guidelines for regulatory measures in experiments. The aim of the present study is to determine the effect of Nephelium lappaceum fruit flesh on acute toxicity and behavioural responses of Catla catla fingerlings. The experimental fish species of Catla catla fingerlings showed acute exposure to Nephelium lappaceum fruit crude powder caused significant non-sensitivity to all concentrations (250, 500, 1000, 2000 and 4000 mg/kg), and the mortality rate was nil. The juvenile Catla catla exposed to various lethal concentrations of Nephelium lappaceum fruit flesh crude powder exhibited normal behavioural responses. Present results finding Nephelium lappaceum fruit flesh crude powder was non-toxic were observed in supplementation to Catla catla fingerlings, based on a maximum concentration of 4000 mg/kg, while it may promote health benefits. This study provided evidence that Nephelium lappaceum fruit was non-toxic, which is classified as practically non-toxic and promotes its consumption by aquatic organisms.